Synovitis scoring in hand osteoarthritis with ultrasonography: the performance of the Global OMERACT/EULAR Ultrasound Synovitis Score (GLOESS) is comparable to synovial thickening alone - Féline P B Kroon; Margreet Kloppenburg; Frits R Rosendaal; Marion C Kortekaas; Maria Antonietta D’Agostino; Coen van der Meulen (RMD Open)
Background Inflammation is increasingly recognised as a treatment target in hand osteoarthritis, and therefore correct measurement of local inflammation is essential. This study aimed to assess ultrasound scoring of synovitis and the additional value of the Global OMERACT/EULAR Ultrasound Synovitis Score (GLOESS) in hand osteoarthritis.Methods Data from the randomised, double-blinded Hand Osteoarthritis Prednisolone Efficacy (HOPE) trial were used. The HOPE trial included patients with painful, inflammatory hand OA, treated with prednisolone or placebo (1:1). Ultrasound was performed in 30 hand joints at weeks 0, 6 and 14. Effusion, synovial thickening and Doppler signal were measured, the GLOESS was calculated from the latter two. Joint tenderness on palpation was assessed semiquantitatively (0–3), soft swelling as present/absent. Changes in ultrasound scores, and their association with change in joint tenderness or soft swelling, were investigated using generalised estimating equations. Effect sizes were calculated.Results Of 92 included patients 79% were women, with mean (SD) age 63.9 (8.8) and body mass index 27.2 (4.6). Synovial thickening was the most prevalent. All ultrasound scores were strongly associated with joint tenderness and soft swelling cross-sectionally. There was no association of change in ultrasound scores with change in tenderness, but there was with change in soft tissue swelling. Synovial thickening and the GLOESS responded to treatment (effect size −0.39 (−0.72 to −0.07), −0.39 (−0.71 to −0.07), respectively).Discussion Various ultrasound scores were associated with joint tenderness and soft swelling. The GLOESS and synovial thickening were both responsive to treatment, but GLOESS was not superior to synovial thickening alone.